2019
DOI: 10.1002/ange.201904156
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Asymmetric Allylic Aromatization Reaction

Abstract: Described herein is an asymmetric allylic aromatization (AAAr) strategy that employs readily accessible equivalents of benzylic nucleophiles in iridium-catalyzed allylic substitution reactions with the concomitant formation of aromatic rings by aromatization. The optimizedr eaction conditions involving ac atalyst derived from ac ommercially available iridium precursor and the Carreira ligand are compatible with equivalents of benzylic nucleophiles derived from 4-or 5-methyloxazoles,5 -methylthiazoles,4 -o r5me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Alternative strategies for the enantioselective (hetero)benzylation of secondary allylic electrophiles include the use of Lewis acid stabilized, deprotonated methyl azaheterocycles, [9] benzylic deprotonation of Cr(CO) 3 activated toluenes followed by decomplexation, [10] fragmentation of 4‐benzyl‐dihydropyridines with photoredox co‐catalysts, [11] and the use of electron‐rich diene nucleophiles that can undergo aromatization upon allylation (Figure 1 a). [12] A recent report established that 4‐benzyl‐dihydropyridines can be used to generate quaternary benzylated stereocenters using α‐aryl allylic carbonate electrophiles; however enantioselectivities remained modest (generally ≈80 % ee ) [13] . We previously developed a decarboxylative approach for the enantioselective benzylation of secondary allylic electrophiles using arylacetic acids as pronucleophiles [14] .…”
Section: Figurementioning
confidence: 99%
“…Alternative strategies for the enantioselective (hetero)benzylation of secondary allylic electrophiles include the use of Lewis acid stabilized, deprotonated methyl azaheterocycles, [9] benzylic deprotonation of Cr(CO) 3 activated toluenes followed by decomplexation, [10] fragmentation of 4‐benzyl‐dihydropyridines with photoredox co‐catalysts, [11] and the use of electron‐rich diene nucleophiles that can undergo aromatization upon allylation (Figure 1 a). [12] A recent report established that 4‐benzyl‐dihydropyridines can be used to generate quaternary benzylated stereocenters using α‐aryl allylic carbonate electrophiles; however enantioselectivities remained modest (generally ≈80 % ee ) [13] . We previously developed a decarboxylative approach for the enantioselective benzylation of secondary allylic electrophiles using arylacetic acids as pronucleophiles [14] .…”
Section: Figurementioning
confidence: 99%
“…Model reactions in the absence of the gold catalyst (Table 1, entry 6) or the organocatalyst (Table 1, entry 7) revealed no reaction or formation of alkylideneoxazoline 5aa as the major product, respectively.T hese results indicated that the gold catalyst responsible for the catalytic cyclization of N-propargylamide,w hile the organocatalyst is essential in enabling the allylation step.T oe xplore whether this transformation went through ag old/organo cooperative [38] or relay [39] catalysis manner,alkylideneoxazoline 5aa and 2a were applied to the standard conditions with or without the gold catalyst, majority of the materials remained intact and no 4aa was observed by the proton NMR spectrum of the reaction mixture (Scheme 2a;Supporting Information, Figures S1 and S2). Moreover,w hen this reaction was conducted under thermal conditions,the ene reaction product 8aa was isolated in 35 %yield, [20,21] contaminated with aromatized oxazole 9aa in 31 %y ield (Scheme 2b). These results ruled out the possibility of as tepwise catalytic relay via alkylideneoxazoline 5aa.Further effort focused on exploration of the identity of the key intermediate that might be generated in situ via gold-catalyzed cyclization.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[10] Alternatively,f ree radical and neutral cross-coupling partners have been employed in allylic benzylation reactions by Yu and You, respectively. [11,12] Nevertheless,the direct and branched selective allylic alkylation with an unstabilized benzyl nucleophile for the installation of electronically unbiased toluene derivatives has not been reported. Herein, we describe the regio-and diastereoselective rhodium-catalyzed allylic alkylation with hard benzylzinc species for the construction of vicinal acyclic ternary/ternary stereogenic centers (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%